Does intellectual capital efficiency spur the financial performance of banks? A comparative analysis of Islamic and conventional banks in Pakistan - Farhad Ahmed Bhatti; Ejaz Aslam; Aziz ur Rehman; Shazia Ashraf; Muhammad Aslam; Malik Shahzad Shabbir (Al-Qanṭara, 2023)
In the contemporary landscape of banking, the concept of intellectual capital efficiency (ICE) has emerged as a pivotal force, embodying the intangible assets that wield remarkable influence over an institution's performance. Therefore, this study aims to comparatively examine the ICE on the financial performance of banks in Pakistan. This study used a panel data structure, which includes data from 16 commercial banks and 5 Islamic banks in Pakistan, over a period of 12 years, from 2009 to 2020. This study employed the GLS estimation model and found that ICE serves as a powerful catalyst for both Islamic and conventional bank to promote their financial performance. However, specific elements of VAIC, such as human capital, and structural capital are more important components for conventional banking and human and relational capital are significant factors that spur the financial performance in Islamic banking. Finally, VAIC is unpredictable and diverse in terms of spurring the bank's financial performance in Pakistan. Our findings suggest that policymakers and top management of banking should pay closer attention to VAIC components, which have the potential to spur the banking financial performance as well as keep them competitive in the financial market.